ANALISIS MINAT SISWA PADA PROGRAM ILMU SOSIAL DALAM MEMILIH LINTAS MINAT BIOLOGI DI SMAN KUBU DAN SMAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Eka Emariza; Arnentis Arnentis; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine students' interest in social science programs in choosing cross-interest Biology at SMAN Kubu and SMAN Kubu Babussalam, Rokan Hilir Regency. The type of research is descriptive research. This research was conducted at SMAN 1 Kubu, SMAN 1 Kubu Babussalam and SMAN 2 Kubu Babussalam in class X (ten). The time of the study started from August to October 2020. The sample in this study was determined by the purposive sampling technique. The sample in the study were 35 students from SMAN 1 Kubu, 36 students from SMAN 1 Kubu Babussalam, 38 students from SMAN 2 Kubu Babussalam with a total of 109 people. Data collection uses online questionnaire distribution techniques through the Google Forms Platform and data collection instruments use questionnaires. The test data of the questionnaire were tested for validity and reliability using the SPSS (Statistical Product and Service Solution) V. 22.00 software program. After the data was collected, it was analyzed descriptively. The results showed that the indicators of student interest in the social science program in choosing cross-interest in biology at the three schools were classified as high with an average of 80%.Key Words: Biology,interest, Social Science